Efficient XML Interchange: Binary Encoding in Data Processing and Integration - Niesler, Andrzej (Advanced Information Technologies for Management – AITM 2009, 2009)
Extensible Markup Language (XML) is the foundation of many modern IT architectures. It is an extremely versatile integration tool and has been adopted in almost every business domain. The variety of applications imposes now the need for thorough analysis on how does the XML-orientation affect the enterprise data processing and integration scenarios. The paper discusses the problem of XML processing efficiency on various stages of the data interchange process. The main focus is on the information representation issue, with a special emphasis put on the binary encoding. As there are many different approaches to serialization of the textual XML, some common integration scenarios arc subjected to the comparative analysis, in order to identify the crucial efficiency factors and implementation constraints. Based on the determined set of criteria, selected technologies are evaluated from the perspective of effective XML implementation strategy.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 85, s. 179-190